CHARACTERISTICS OF INFERTILE PATIENTS WITH OVULATORY DYSFUNCTION AND THEIR RELATION TO BODY MASS INDEX - Sadia, Shamsunnisa; Waqar, Fareesa; Akhtar, Tasneem; Sultana, Sadia (Journal of Ayub Medical College Abbottabad, 2009)
Background: Ovulatory dysfunction is a group of disorders with variable clinical presentations occasionally having serious long-term adverse effects. It accounts for 30% of female fertility problems. Evidence suggests an association between an individual’s weight and disorders of ovulation. The objective of our study was to describe the clinical and hormonal profile of subfertile women with ovulatory dysfunction in relation to their body mass index (BMI). Methods: This prospective, descriptive study was carried out in Mother and Child Health Centre, PIMS, Islamabad and Railway hospital, Rawalpindi from April 2001 to March 2007. One hundred & thirty eight infertile patients with ovulatory dysfunction were included. The clinical data including BMI of each patient was recorded in addition to reports of investigations comprised of cervical smear, pelvic ultrasound and hormonal profile. Results: Primary infertility was found in 61% while secondary in 39% of the patients. The mean age was 29 years and mean duration of infertility was 6 years. Menstrual pattern was normal in 56.5%. BMI was normal in 30.4% while most patients were overweight and obese. Prolonged cycles, history of systemic endocrine disorders, abnormal vaginal discharge, hirsutism, polycystic ovarian morphology and hormonal abnormalities were more frequent in patients with increased BMI. During the study period, 21.7% of the women conceived. Conclusion: Infertile patients with ovulatory dysfunction present more frequently with primary infertility. They usually have higher than required BMI. Oligomenorrhoea amenorrhoea, hirsutism and hormonal abnormalities are more frequent in overweight than infertile patients with ovulatory dysfunction having a normal BMI. Keywords: Infertility, Ovulatory Dysfunction, Clinical Characteristics, Body mass index, BMI